Penguatan Kompetensi Guru Melalui Workshop Pembelajaran Mendalam (Deep Learning) di MI Nurul Falahiyah Kabupaten Tangerang - Adnan Bafaqih; Feny Nida Fitriyani; Miftachudin Miftachudin; Zubaidi Zubaidi; Fitriana Siregar; Asma’Ashila Yumna (Fakultas Tarbiyah dan Keguruan, 2026)
The quality of learning in Islamic elementary schools (madrasahs) is greatly influenced by teachers’ ability to design meaningful and student-centered learning experiences. Based on preliminary observations conducted at MI Nurul Falahiyah, Tangerang Regency, the learning process was still predominantly characterized by a teacher-centered approach focused on content delivery, which had not yet optimally fostered students’ critical and reflective thinking skills. This community service program aimed to enhance teachers’ understanding and pedagogical competence through a deep learning workshop. The program was implemented using a participatory-educational approach consisting of needs assessment, program preparation, workshop implementation, interactive discussions, and reflective evaluation. The participants were all teachers of MI Nurul Falahiyah. Data were collected through observation, documentation, and participant reflections and were analyzed using a qualitative descriptive approach. The findings revealed an improvement in teachers’ understanding of the deep learning concept, a shift in teaching paradigms from knowledge transmission toward meaningful learning, and increased motivation to implement instructional strategies that promote students’ critical, reflective, and contextual thinking skills. The program received positive responses from the madrasah community and contributed to strengthening teacher professionalism at MI Nurul Falahiyah in addressing the challenges of 21st-century education.